Digital Transformation: Digital Maturity, Competitive Strategy, and Sustainable Business Model in Construction Industry. A Literature Review - Gilang, Wildan; Jane, Orpha (Dinasti International Journal of Digital Business Management, 2024)
In this digital era, the use of digital technologies is a must to implement in any industry, including construction industry. There are many technologies that have been implemented by construction companies in their digital transformation agenda like BIM, Artificial Intelligence, IoT, Big Data & Analytics, 3D printing, etc. Prior to implement those digital technologies, construction company should develop a comprehensive and holistic digital transformation strategy. The purpose of this research is intended to give recommendations in defining the dimension of digital maturity assessment and aspects to be well-thought-out in creating digital strategy. Literature review methodology is applied with reviewing books and journals that discussed the digital maturity assessment and strategy development. In conclusion, the digital transformation strategy development is required the maturity assessment first to understand the current digital transformation. The digital transformation strategy is recommended to consider the impact to the surrounding environment in order to give the value not only for the construction company itself.